Systematic Literature Review : Evalusi Program Jaminan Kesehatan Nasional (JKN) Di Indonesia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The National Health Insurance Program (JKN) is a government policy aimed at providing health protection for all Indonesians through fair, equitable, and sustainable healthcare services. However, its implementation still faces various challenges and issues. This study aims to analyze the implementation of the JKN program in Indonesia using a systematic literature review and the CIPP (Context, Input, Process, Product) evaluation model. Ten scientific articles published between 2021 and 2025 were selected and analyzed based on established inclusion and exclusion criteria. The results indicate that in the context aspect, there are still problems, such as a large number of participants with inactive membership status and a low level of public understanding of their rights and obligations as JKN participants. In the input aspect, obstacles faced include limited health workers, uneven distribution, and inadequate facilities and infrastructure. Furthermore, in the process aspect, various obstacles were found, such as long service queues, complex administrative procedures, disruptions in the medical record system, and the suboptimal use of digital-based services. Meanwhile, in terms of products, the National Health Insurance (JKN) program has proven effective in improving public access to healthcare services, although service quality remains uneven, drug availability remains unstable, and the BPJS Kesehatan financing system still faces several challenges. Overall, the JKN program has had a positive impact on the community, but comprehensive improvements are still needed, particularly in strengthening governance, equitable access to services, and improving the quality of healthcare services.